Energy-Efficient Thermal Management: Advanced Cooling Techniques for Electronics, Automotive, and Aerospace Applications - Shubham Mishra (International Journal of Energy and Thermal Applications, 2025)
The growing demand for energy-efficient systems across diverse industrial sectors, including electronics, automotive, aerospace, and renewable energy, has elevated the importance of advanced thermal management techniques. Effective heat dissipation is critical not only for maintaining optimal operating conditions in electronic devices but also for enhancing the performance and reliability of broader energy and mechanical systems. Inadequate thermal management can compromise energy efficiency, reduce component lifespan, and increase environmental impact. This review examines the principles, classifications, and comparative performance of both passive and active cooling techniques, with a focus on their applications in energy and thermal systems. Passive approaches, such as heat sinks, thermal interface materials (TIMs), phase change materials (PCMs), and heat pipes, offer sustainable and low-maintenance solutions. Active methods, including forced air convection, thermoelectric cooling, and liquid cooling, provide dynamic thermal regulation suitable for variable energy loads. Emerging innovations such as vapor chambers, nanomaterial-enhanced TIMs, and AI-driven smart cooling systems are also discussed, with an emphasis on their role in advancing the efficiency and sustainability of next-generation energy and thermal applications. The study presents a comparative analysis of cooling strategies across key performance metrics, identifies current challenges, and outlines future directions. This work aims to contribute toward the development of intelligent, energy-efficient thermal management solutions that support the evolving demands of modern energy, mechanical, and electronic systems.
Keywords: Mechanical systems; Thermal energy; energy-efficient thermal management; heat transfer in energy systems; sustainable cooling